Description of Criminal Actions and The Legal Consequences Given against Criminal Actions - Alif Nurochman Hakim; K Kuswardani (Proceeding International Conference Restructuring and Transforming Law, 2023)
Entering the era of digitalization, ease of access and effectiveness of work on the network it can be increasingly felt. With this, life exists increasingly instantaneous with the presence of knowledge and technology. Then on the side Apart from that, we also need to realize that there are many things that are increasingly complex arise. It is as if everything present on this earth is correlated with each other and also among one another with others without clarity between the boundaries of interaction permitted or prohibited. Then indirectly this causes crime to increase. Many crimes occurred making people more aware of the importance of protecting each other each individual. One form of protection is attachment to law. In Indonesia itself, law is a very fundamental thing regulate state life. Equivalent to Article 1 Paragraph 3 that is Indonesia is a state of law.This research article applies normative juridical research methods by examining library materials, namely primary and secondary legal materials. The data collection technique uses library research, by collecting data and information or legal materials related to the substance of the research. After the legal materials are collected, analysis is carried out and appropriate conclusions are drawn regarding the problems contained in the problem formulation. This research applies data analysis techniques using deductive logic. This conclusion is based on criminal regulations. Criminal problems are still widespread, this will be analyzed according to existing regulations, from a legal perspective in order to understand the essence and intent in resolving the legal problems discussed in this research.